Liberdade e incondicionalidade do dever na filosofia moral de Kant - Rauber, Jaime José (2013)
The aim of this thesis is to show that Kant's moral philosophy, which finds its basis in the concept of freedom is established with absolute independence of any appreciable influence. Only when man is able to determine their willingness to unconditionally, ie, free from everything empirical effectively becomes free. Within this perspective, there is no room for exceptions to the duty claimed on the basis of empirical circumstances of the shares, as this would lead to a contradiction of pure practical reason with itself. This absoluteness of duty does V. Hösle criticize Kant's moral philosophy insensitivity. At first glance, a response to criticism of V. Hösle seems to be anticipated by Kant with the distinction between duties of strict obligation and duties of obligation can, but research has shown that Kant's moral philosophy remains unconditional and there is no room for exceptions to duty or under or in connection with legal ethics. Nevertheless, the moral philosophy of Kant touches indirectly sensitivity insofar as we are affected and feel the effects of the moral law within us, but this in no way contradicts the purity of his thought.